Bilateral inverted papilloma: Case report and literature review - Mohammed Amine Rabhi; Achraf Amine Sbai; Drissia Benfadil; Azzedine Lachkar; Adil Abdenbi Tsen; Fahd Elayoubi (Radiology Case Reports)
Inverted papilloma is a rare, benign epithelial tumor of the nasal and sinus cavities with an unclear etiology. It usually presents as unilateral nasal obstruction. Diagnosis is histological, and treatment is primarily surgical. We describe a 72-year-old patient with persistent bilateral nasal obstruction. Examination revealed a greyish-pink, multi-lobed mass in both nasal cavities pressing on the hard palate. Imaging (CT and MRI) showed a cerebriform mass extending through the nasal cavities and into the nasopharynx, causing bone destruction without intracranial or intra-orbital spread. Histopathology confirmed a bilateral inverted papilloma without malignancy. Inverted papilloma comprises less than 4% of primary nasal tumors. It is noted for high local aggressiveness, frequent recurrences, and potential association with squamous cell carcinoma. Imaging (CT and MRI) aids in staging and selecting the surgical approach—endoscopic, external, or combined. Close surveillance via endoscopy and imaging is crucial. Although benign, inverted papilloma is highly invasive. Accurate diagnosis and complete surgical removal are essential to minimize recurrence risk.